COMPARATIVE STUDY OF REQUEST STRATEGIES IN BRITISH ENGLISH AND UZBEK (Ustozlar uchun, 2026)
This thesis examines request strategies in British English and Uzbek from a cross-cultural pragmatic perspective. Requests are speech acts used to ask someone to do something, and they reflect social norms, politeness conventions, and cultural values. British English tends to employ indirect and conventionally polite forms such as modal verbs (“Could you open the window?”), whereas Uzbek often uses honorific expressions and culturally appropriate markers such as iltimos (“please”) and respectful verb endings. The analysis demonstrates that both languages prioritize politeness, but they realize it through different linguistic and pragmatic means.